2012
DOI: 10.3168/jds.2011-4870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sources and levels of dietary gossypol on gossypol residues in plasma and milk of lactating cows

Abstract: Free gossypol residues in tissues or milk from feeding whole cottonseed and cottonseed meal were measured for their effect on health of dairy cows and humans. Forty lactating cows were randomly assigned to 5 treatments in a 60-d experiment to investigate the effects of sources and dietary level of gossypol on plasma and milk gossypol concentrations in lactating cows. Five experimental diets had identical net energy for lactation and crude protein content on a dry matter (DM) basis. Soybean meal was the main pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…In the present experiment, the content of gossypol in WCS2 and WCS3 was consistent with the above results, but FG in WCS1 was greater than the above results, which may be related to WCS varieties and other factors. Wang et al ( 2012 ) reported that the content of FG in CSM was 0.9 g/kg, which was greater than the FG content of CSM samples of present study. The FG content of CSH sample in the present experiment was close to the results of Viana et al ( 2015 ).…”
Section: Discussioncontrasting
confidence: 72%
“…In the present experiment, the content of gossypol in WCS2 and WCS3 was consistent with the above results, but FG in WCS1 was greater than the above results, which may be related to WCS varieties and other factors. Wang et al ( 2012 ) reported that the content of FG in CSM was 0.9 g/kg, which was greater than the FG content of CSM samples of present study. The FG content of CSH sample in the present experiment was close to the results of Viana et al ( 2015 ).…”
Section: Discussioncontrasting
confidence: 72%
“…High gossypol diets also decreased milk production and milk protein and increased the somatic cell score in lactating cows ( Higginbotham et al., 2004 ). Fortunately, gossypol residue in milk was far below the maximum residue limits of FG specified by the Food and Agriculture Organization and the US Food and Drug Administration, which are set at 600 and 450 mg/kg, respectively ( Wang and Plhak 2004 ; Zhong 2007 ; Wang et al., 2012 ).…”
Section: Gossypol In Cottonseed By-products and Its Toxicity To Ruminantsmentioning
confidence: 97%
“…Van gossypol (katoenplant) is bekend dat het in lage hoeveelheden overgedragen kan worden naar plasma en melk (Wang et al, 2012). Overdracht van indospicine (Indigofera plant)(aminozuur, arginine analoog) naar vlees is gemeld in Australië (FitzGerald et al, 2011;Tan et al, 2014).…”
Section: Overdracht Naar Dierlijke Productenunclassified